A STUDY ON CHALLENGES AND FUTURE OF NEOBANKS IN INDIA - ASMA, UMME; MARY JOHNSON, JOHNSY; GEORGE, GISA (The journal of contemporary issues in business and government, 2022)
The financial industry embraces digital services in every aspect of its operations as the globe enters the digital age. To a large extent, customers in financial institutions and banks increasingly rely on digital services. A neobank is a financial institution that is solely accessible online. Compared to typical banks, neobanks tend to have limited functions.Neobank’s services are centeredon the customer’s needs and are supported by cutting-edge technology. The Neo bank uses an Application Programming Interface (API), a computer-based programming language that makes it possible to link together different software applications.Neobanks cater to a younger, more tech-savvy demographic familiar with making electronic payments. The banking industry’s future lies with Neobank. Customers and traditional banks can now seamlessly conduct their business thanks to a variety of services provided by the platform.The digital revolution is here to stay. Investment in enabling technologies is expected to rise significantly in the post-pandemic world. The study aims in fulfilling the following objective: 1. To comprehend neo banking's structure. 2. To examine the potential problems that Neo Banks is facing. This study involves a descriptive research design that incorporates qualitative and quantitative data from a variety of secondary sources. The situation of Neo Banks and Traditional Banks is also analyzed using a comparative method. The new face of the Indian banking system is the neobanks. They correctly identified the gap between users' needs and the services provided by traditional banks. They provide services that ensure that customers receive consistent service. They also make certain that the consumers' transactions are free of hazel.